Nonlinear Wigner solid transport over superfluid helium under AC conditions - Monarkha, Y.P.; Kono, K. (Физика низких температур, 2009)
Nonlinear transport properties of the two-dimensional Wigner solid of surface electrons on superfluid helium are studied for alternating current conditions. For time-averaged quantities like Fourier coefficients, the field-velocity characteristics are shown to be qualitatively different as compared to that found in the DC theory. For a spatially uniform current we found a general solution for the field-velocity relationship which appears to be strongly dependent on the current frequency. If the current frequency is much lower than the ripplon damping parameter, the Bragg–Cherenkov resonances which appear at high enough drift velocities acquire a distinctive saw-tooth shape with long right-side tails independent of small damping. For current frequencies which are close or higher than the ripplon damping coefficient, the interference of ripplons excited at different time intervals results in a new oscillatory (in drift velocity) regime of Bragg–Cherenkov scattering.